Influencia de los juegos etnomatemáticos en el aprendizaje del pensamiento lógico matemático de los niños de Preparatoria. - Logroño Galárraga, María Fernanda (2023)
Indirectly related to mathematical logical thinking, this is caused by the lack of innovative strategies, for which the study maintains as a general objective to evaluate the influence of ethnomathematical games on the learning of mathematical logical thinking of high school children of the Intercultural Educational Center and bilingual "Sumak Kawsay", for the development of the study a qualitative methodology was used, with a descriptive and analytical approach through the use of data collection tools such as checklists, interviews and field observations; The results allowed us to recognize the shortcomings within the classroom, as well as the skills that must be reinforced with the help of teachers and the appropriate methodologies in each case. For this reason, the proposed Ethnomathematical Games Guide for the learning of mathematical logical thinking of high school children of the Intercultural and Bilingual Educational Center "Sumak Kawsay" which is entitled "The Incredible World of Mathematics", seeks to help teachers to define new work strategies using ethnomathematical games so that students develop mathematical logical thinking using games and resources that are in their environment. KEYWORDS: Learning, Development, Teaching, Ethnomathematical Games, Mathematical Logical Thinking Edison Santiago Sanguña Loachamin with identity card number: 1713978284 Graduate in: Educational Sciences, Plurilingual Mention with SENESCYT registration number: 1045-10-71/MDT-3104-CCL-258366; I CERTIFY having reviewed and approved the translation into English of the summary of the research work with the title: The Influence of ethnomathematical games on the learning of logical mathematical thinking of High School children by: Logroño Galárraga María Fernanda, aspiring Master of Education